2004
DOI: 10.1007/s00535-003-1250-4
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas head carcinoma with total fat replacement of the dorsal exocrine pancreas

Abstract: We report a case of pancreas head carcinoma associated with fat replacement of the body and tail. A 68-year-old man presented with obstructive jaundice and was admitted to our hospital. Ultrasonography and computed tomography showed pancreas head tumor with a neighboring cystic lesion and fatty replacement of parenchyma of the pancreas body and tail. By endoscopic retrograde pancreatography, abruption of the main pancreatic duct and the presence of an accessory duct were detected. After percutaneous transhepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Treatment of pancreatic neoplasia in the setting of DAP does not deviate from current management guidelines [ 13 ]. Surgical resection of pancreatic tumors in patients with DAP often requires resection of the remaining pancreatic tissue, with a high rate of insulin dependent diabetes mellitus and exocrine insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of pancreatic neoplasia in the setting of DAP does not deviate from current management guidelines [ 13 ]. Surgical resection of pancreatic tumors in patients with DAP often requires resection of the remaining pancreatic tissue, with a high rate of insulin dependent diabetes mellitus and exocrine insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…18 Proposed criteria for confirming true congenital DAP as opposed to fatty replacement include the complete absence of exocrine features, acinar cells, and islets of Langerhans on histologic examination. 19 Suggested radiologic criteria to diagnose dorsal agenesis of the pancreas have included the lack of a dorsal and transverse pancreatic artery on angiography (rarely performed) and the absence of an accessory pancreatic duct on ERP. 19 However, the most common means of diagnosis is by cross-sectional imaging (CT or MRI/MRCP).…”
Section: Discussionmentioning
confidence: 99%
“…19 Suggested radiologic criteria to diagnose dorsal agenesis of the pancreas have included the lack of a dorsal and transverse pancreatic artery on angiography (rarely performed) and the absence of an accessory pancreatic duct on ERP. 19 However, the most common means of diagnosis is by cross-sectional imaging (CT or MRI/MRCP).…”
Section: Discussionmentioning
confidence: 99%
“…2, 3, 4 A few pathologic studies of patients with pancreatic cancer have demonstrated fatty infiltraton (FI) in the pancreas parenchyma. 5, 6 FI in the pancreas is positively correlated with age, body mass index (BMI), and a history of DM. 7, 8, 9 …”
Section: Introductionmentioning
confidence: 99%